Photodynamic therapy for skin carcinomas: A systematic review and meta-analysis - Ou-Yang, Yun; Zheng, Yaowu; Mills, Kerry E. (Frontiers in Medicine, 2023)
Background: Photodynamic therapy (PDT) is increasingly used for the treatment of basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). However, it is unknown whether photodynamic therapy is more effective than other commonly used treatment modalities for these cancers. Purpose: The aim of this study was to determine the relative efficacy and safety of PDT compared with placebo or other interventions for the treatment of skin carcinomas. Methods: Searches were performed in PubMed, Web of Science, Embase, and the Cochrane Central Register of Controlled Trials databases. We included randomized controlled trials comparing the PDT with other interventions in adults skin BCC or SCC that reported on lesion response, recurrence, cosmetic appearance, or safety outcomes. Results: Seventeen unique randomized controlled trials, representing 22 study arms from 21 publications were included. The included trials included 2,166 participants, comparing methylaminolevulinic (MAL) PDT (six studies) or aminolevulinic acid (ALA) PDT (two studies). Comparators included placebo, surgery, hexaminolevulinic (HAL) PDT, Erbium:yttrium-aluminum-garnet ablative factional laser (YAG-AFL) PDT, fluorouracil, and imiquimod. Mantel-Haenszel fixed effects risk ratios were calculated for response, recurrence, cosmetic outcomes, and adverse events. MAL-PDT had similar response rates to surgery, ALA-PDT, fluorouracil and imiquimod at three- and twelve months post-intervention. The rate of recurrence was similar, showing few differences at twelve months, but at later time points (24–60 months), fewer lesions recurred with surgery and imiquimod than with PDT. PDT also caused more adverse events and pain than other interventions. However, PDT treatment was more likely to receive a “good” or “excellent” rating for cosmetic appearance than surgery or cryotherapy. Conclusion: This systematic review and meta-analysis demonstrates that the choice of treatment modality for BCC or SCC is best chosen in the context of the location and size of the lesion, the socioeconomic circumstances of the patient, as well as the patient’s preferences. Systematic review registration: CRD42022368626